The Role of Foot-Eye Coordination and Leg Muscle Strength in Football Shooting Performance: A Correlational Analysis Among Youth Athletes - Charisma Maranatha Sitanggang; Muhammad Ikram Salim; Alan Alfiansyah Putra Karo Karo; Mitchell Wayne (INSPIREE: Indonesian Sport Innovation Review, 2024)
The  purpose  of  the study. This study aimed to investigate the relationship between foot-eye coordination, leg muscle strength, and football shooting accuracy among youth football players, and to determine which factor contributes more significantly to shooting performance. Materials and methods. Twenty-four male youth football players (aged 16-18 years) from Mabar Hilir Club, Medan City, participated in this cross-sectional correlational study. Participants underwent three assessment protocols: (1) foot-eye coordination using a modified ball control test, (2) leg muscle strength using isokinetic dynamometry, and (3) shooting accuracy using a standardized target shooting test. Data were analyzed using Pearson correlation coefficients and multiple regression analysis with SPSS v27. Results. Significant positive correlations were found between shooting accuracy and foot-eye coordination (r = 0.742, p < 0.001) and leg muscle strength (r = 0.628, p < 0.001). Multiple regression analysis revealed that foot-eye coordination explained 55.1% of the variance in shooting accuracy, while leg muscle strength contributed an additional 16.3% (R² = 0.714, p < 0.001). Conclusions. Foot-eye coordination demonstrates a stronger association with football shooting accuracy than leg muscle strength in youth athletes. Training programs should prioritize the development of coordinative abilities alongside strength training to optimize shooting performance.